Compassion through technology: Digital empathy concept analysis and implications in nursing - Ebtsam Aly Abou Hashish (Digital Health)
Objective Digital empathy is an emerging concept in telehealth nursing, emphasizing emotional engagement and compassionate communication in virtual care settings. Despite its importance, digital empathy remains underexplored. This concept analysis aims to define digital empathy in nursing, explore its key attributes, antecedents, consequences, challenges, and actionable recommendations for practice. Methods Using Walker and Avant's eight-step framework, a comprehensive literature review was conducted on digital empathy in telehealth nursing. A total of 52 sources were reviewed, comprising 46 research articles, four books, and two web pages, published between 2000 and 2024. Results This concept analysis identifies key attributes of digital empathy in nursing, including authenticity, trust-building, communication effectiveness, emotional engagement, adaptability, technological proficiency, and cultural sensitivity critical for meaningful connections in telehealth. Antecedents encompass digital literacy, emotional intelligence, supportive infrastructures, and cultural competence, emphasizing individual, contextual, and organizational factors. Consequences include enhanced patient satisfaction, trust, adherence to treatment, improved nurse well-being, and organizational benefits such as team cohesion and reduced staff turnover. Challenges such as cultural variability, technological limitations, and the lack of validated measurement tools highlight barriers to effective implementation. Conclusion This concept analysis underscores the vital role of digital empathy in telehealth nursing. By incorporating its attributes and antecedents, healthcare organizations can enhance patient outcomes and foster supportive, patient-centered environments. Addressing measurement and technological gaps will be pivotal in fully realizing the benefits of digital empathy in telehealth. Actionable recommendations include implementing targeted training, developing standardized tools, and leveraging artificial intelligence advancements to enhance empathetic communication in telehealth.